Adult cancer patients' perception of social support in non-profit electronic counselling services: a descriptive qualitative study. Issue 3 (4th May 2018) - Yli-Uotila, Tiina; Kaunonen, Marja; Pylkkänen, Liisa; Suominen, Tarja
Abstract : Background : Cancer patients may need to seek support from electronic sources because their needs are not fulfilled in the hospital settings. Objectives : The explore cancer patients' perception of social support in non-profit electronic counselling services. Design : A qualitative descriptive cross-sectional design. Methods : The data were collected from adult cancer patients who had utilized non-profit electronic counselling services. The interviews were conducted face-to-face or over the phone and analysed with inductive content analysis. Findings : Two patterns were identified: (1) a contact person that will ensure a personalized matching type of support to enhance patients' ability to cope with cancer if necessary and (2) deficient resources of the electronic counselling services to provide the matching type of support to enhance patients' coping with cancer. Conclusions : For patients to be able to successfully cope with their disease, it is essential that the electronic social support type matches each patient's specific needs.